Experimental and Computational Approaches for the Structural Study of Novel Ca-Rich Zeolites from Incense Stick Ash and Their Application for Wastewater Treatment - Virendra Kumar Yadav (Hindawi - SAGE Publishing, 2021)
At present, chemical Si/Al sources are mainly used as precursor materials for the manufacturing of zeolites. Such precursor materials are quite expensive for commercial synthesis. Here, we have reported the synthesis of Ca-based zeolite from incense stick ash waste by the alkali-treatment method for the first time. Incense stick ash (ISA) was used as a precursor material for the synthesis of low Si zeolites by the alkali-treatment method. The as-synthesized zeolites were characterized by various instruments like particle size analyzer (PSA), Fourier transform infrared (FTIR), X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), electron diffraction spectroscopy (EDS), transmission electron microscopy (TEM), and X-ray fluorescence (XRF). FTIR and XRD helped in the identification of the microstructure and crystalline nature of the zeolites and also confirmed the synthesis of Ca-based zeolite with two thetas at 25.7°. The microscopic analysis by FESEM and TEM exhibited that the size of synthesized Ca-rich zeolites varies from 200 to 700 nm and they are aggregated and cuboidal in shape. Additionally, structural, electronic, and density of states’ characteristics of gismondine (Ca2Al4Si4O16·9H2O) structures were evaluated by computational simulations (first principle, density functional theorem). The structural optimization of structures was carried out in the first stage under the lowest condition of total energy and forces acting on atoms for the lattice constant, as well as the available experimental and theoretical findings. The present research approach predicted the transformation of ISA waste into a value-added mineral, i.e., zeolite, which was further used for the removal of both heavy metals and alkali metals from fly ash-based wastewater using inductively coupled plasma-optical emission spectroscopy (ICP-OES).